Late Holocene long arid phase in the Indian subcontinent as seen in shallow sediments of the eastern Arabian Sea - Saravanan, Ponnusamy; Gupta, Anil K.; Zheng, Hongbo; Panigrahi, Mruganka K.; Prakasam, Muthusamy (Journal of Asian Earth Sciences, 2019)
Multi-proxy record of benthic and planktic foraminifera, total organic carbon and carbon and oxygen isotope ratios from Core SK291/GC15, off the coast of Goa, eastern Arabian Sea reveals significant paleoceanographic and paleoclimatic turnovers during ~6000 to 1700 calibrated years before the Present (cal yr BP). Benthic foraminiferal census data was analyzed with multivariate techniques including factor and cluster analyses of highest ranked species from the studied core that enabled to identify seven biofacies. The record suggests centennial to millennial-scale changes in the surface conditions driven by monsoon-linked upwelling in the eastern Arabian Sea during the studied interval. Various benthic biofacies combined with isotope and planktic foraminiferal data suggest that depletion of dissolved oxygen and increase in organic productivity in the study area was caused by intense monsoonal upwelling since the middle Holocene. The results suggest that during 5400–4700 and 3000–2500 cal yr BP the southwest (SW) monsoon was strong leading to intense upwelling in the study area as reflected by increased Globigerina bulloides percentages. These were generally warmer intervals in the northern hemisphere. The SW monsoon significantly weakened (abrupt decrease in G. bulloides population) during 4700–3400 cal yr BP roughly coinciding with a long arid phase in the Indian subcontinent and a cold interval in Europe. Our record suggests an abrupt increase in SW monsoon intensity during ~3000 to 2500 cal yr BP, when a pronounced change in benthic biofacies is also noted that suggests a major shift in the sub-surface conditions. Our data document a prolong weak SW monsoon phase beginning at ~4600 cal yr BP, little earlier than 4.2 ka event, in the eastern Arabian Sea.